Functional Outcome Measurement in Patients with Lower-Extremity Soft Tissue Sarcoma: A Systematic Literature Review - Kask, Gilber; Barner-Rasmussen, Ian; Repo, Jussi Petteri; Kjäldman, Magnus; Kilk, Kaarel; Blomqvist, Carl; Tukiainen, Erkki Juhani (Annals of surgical oncology, 2019)
Background The importance of functional outcome (FO) in the treatment of patients with extremity soft tissue sarcoma (STS) has been increasingly recognized in the last three decades. This systematic review aimed to investigate how FO is measured in surgically treated lower-extremity STS patients. Methods A systematic search of PubMed, Web of Science, and Scopus was performed based on the PRISMA guidelines. The methodologic quality of the publications was measured using the MINORS tool. The results from the included studies examining measurement types, measures, and time of FO measurement were compiled. The FO pooled mean and standard deviation were calculated as a weighted average for the groups. The validity of the applied measures is reported. Results The literature search found 3461 publications, 37 of which met the inclusion criteria. The measurement types used were clinician-reported outcomes ( n = 27), patient-reported outcomes ( n = 20), and observer-reported outcomes ( n = 2). The most frequently used measures were the Toronto Extremity Salvage Score (TESS) ( n = 16) and the Musculoskeletal Tumor Society (MSTS) score 1993 ( n = 12). The postoperative FO was relatively good. The pooled mean TESS and MSTS 1993 scores were respectively 83.3 and 86.2 (out of 100). Of the 10 previously reported measures, 3 provide validated FO scores. The methodologic quality of publications was generally low. Conclusions Based on this systematic review, several different methods exist for assessing FO in patients with lower-extremity sarcoma. The most frequently used measure is a validated TESS. The postoperative FO of patients with lower-extremity STS seems to increase to the preoperative baseline level during long-term follow-up evaluation.